2018
DOI: 10.1080/01621459.2018.1442341
|View full text |Cite
|
Sign up to set email alerts
|

Variance Change Point Detection Under a Smoothly-Changing Mean Trend with Application to Liver Procurement

Abstract: Literature on change point analysis mostly requires a sudden change in the data distribution, either in a few parameters or the distribution as a whole. We are interested in the scenario that the variance of data may make a significant jump while the mean of data changes in a smooth fashion. It is motivated by a liver procurement experiment with organ surface temperature monitoring. Blindly applying the existing change point analysis methods to the example can yield erratic change point estimates since the smo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 61 publications
0
30
0
Order By: Relevance
“…We used variance change point detection using the R package “changepoint” to determine significant change points in our time series data. We chose to use variance as opposed to mean to better identify significant jumps in heart rate changes as opposed to using the mean that addresses distribution changes in a smoother fashion (Gao et al, 2018). To test imputation performances, we randomly deleted intervals from one recorded heart rate data column.…”
Section: Initial Methodologymentioning
confidence: 99%
“…We used variance change point detection using the R package “changepoint” to determine significant change points in our time series data. We chose to use variance as opposed to mean to better identify significant jumps in heart rate changes as opposed to using the mean that addresses distribution changes in a smoother fashion (Gao et al, 2018). To test imputation performances, we randomly deleted intervals from one recorded heart rate data column.…”
Section: Initial Methodologymentioning
confidence: 99%
“…• To test for a variance change point in the presence of a non-constant mean, a possible test statistic can be constructed by using Q (m) = i D 2 i /n with parameters chosen to minimize the long-run variance of log Q (m) , where D i is our proposed mth order difference statistics. This test could be used as an alternative to the recent work by Gao et al (2019).…”
Section: Optimal Parameters Selectionmentioning
confidence: 99%
“…Frick et al (2014) suggested a simultaneous multiscale change-point estimator (SMUCE) by solving an optimization problem, Yao and Au (1989) proposed a penalized least squares-based approach for mean changes. A weighted least squares function-based method was suggested by Gao et al (2018). Harchaoui and Levy-Leduc (2010) proposed a LASSO-based approach.…”
Section: Introductionmentioning
confidence: 99%